Aspiration Before Tissue Filler—An Exercise in Futility and Unsafe Practice. (29th January 2021) - Goodman, Greg J; Magnusson, Mark R; Callan, Peter; Roberts, Stefania; Hart, Sarah; Lin, Frank; Rahman, Eqram; McDonald, Cara B; Liew, Steven; Porter, Cath; Corduff, Niamh; Clague, Michael
Abstract: Background: Aesthetic physicians rely on certain anecdotal beliefs regarding the safe practice of filler injections. These include a presumed safety advantage of bolus injection after a negative aspiration. Objectives: The authors sought to review and summarize the published literature on inadvertent intravascular injection of hyaluronic acid and to investigate whether the technique of aspiration confers any safety to the practitioner and the patient. Methods: Pertinent literature was analyzed and the current understanding of the safety of negative and positive aspiration outlined. Results: The available studies demonstrate that aspiration cannot be relied on and should not be employed as a safety measure. It is safer to adopt injection techniques that avoid injecting an intravascular volume with embolic potential than utilize an unreliable test to permit a risky injection. Conclusions: To prevent intravascular injection, understanding "injection anatomy" and injection plane and techniques such as slow, low-pressure injection are important safety measures. Assurance of safety when delivering a bolus after negative aspiration does not appear to be borne out by the available literature. If there is any doubt about the sensitivity or reliability of a negative aspiration, there is no role for its utilization. Achieving a positive aspiration would just defer the risk to the next injection location where a negative aspiration would then be relied on. Level of Evidence: 4: